Ethical considerations in dealing with CNV information - Tabor, Holly (Henry Stewart Talks, 2010)
Why focus on CNVs?, Existing guidelines on returning results, National Bioethics Advisory Commission, UK Biobank, NIH guidelines, Arguments FOR returning CNV results, Arguments AGAINST returning CNV results, Avoiding CNV exceptionalism, What results mean to families, What we still need to know